Concrete wedge and coarse sand coating shear connection system in GFRP concrete composite deck. (1st July 2016) - Sarir, Payam; Shen, Shui-Long; Arulrajah, Arul; Horpibulsuk, Suksun
Highlights: Numerical investigation on deflection of GFRP concrete deck using concrete wedges. We proposed interface element properties as a shear bond between GFRP and concrete. FEM results show GFRP is more brittle than the steel. GFRP concrete fails after elastic level with no ductility. We proposed an equation to calculate deflection of GFRP concrete composite deck. Abstract: In recent years, Glass Fiber-Reinforced Polymer (GFRP) has become a widely used material in Fiber-Reinforced Polymer (FRP) composite structures. Several studies have been performed on the bonding methods of FRP sheets and plates, but limited research has been undertaken on the critical shear connection systems for innovative GFRP concrete composite bridge decks structures. Coarse sand coating shear connection systems for GFRP structures show strong bondage in the shear direction but poor grip in the normal direction. An innovative concrete wedge system, supplementary to coarse sand coating overcomes the normal split between GFRP panel and concrete, in composite bridge deck structures. This study presents a finite element (FE) investigation on GFRP concrete composite deck using a concrete wedge shear connection system based on existing experimental evaluation. In this research, the thickness of the GFRP module was varied and the deflection behaviour of GFRP concrete composite deck was furthermore studied. FE results indicate that thickness increments of the GFRP module significantly reduce the mid-span deflection of the composite deck and subsequently increase the ultimate load. In order to investigate the interaction behaviour between GFRP and concrete in the numerical analysis, a structural interface element is proposed for finite element modelling (FEM) analysis. In order to undertake a rapid evaluation of deflection of the composite deck, an equation is proposed to estimate the deflection at the mid-span of the GFRP composite bridge deck based on the FEM results. In addition, the GFRP composite bridge deck was numerically analysed using light-weight concrete (LWC) and results were compared with GFRP composite deck with conventional concrete. The results indicate that using LWC increases the ultimate load proportionally till failure.